The ability of pre-service teachers to design learning plans-based on the principles of Understanding by Design (UbD) using the Learning Management System platform - Jenny Indrastoeti Siti Poerwanti; Sri Marmoah; Diana Sinziana Duca (Universitas Sebelas Maret, 2025)
One of the popular platforms that is widely used in online learning in schools and universities today is a Learning Management System (LMS). LMS serves as a comprehensive platform used in online learning, facilitating educational engagement between educators and learners in remote instruction contexts. The aim of this investigation is to describe the ability of pre-service teachers to design learning designs based on UbD principles through the Learning Management System (LMS) and describe the Involvement of Pre-Service Teachers in using LMS. This study uses descriptive qualitative methods, data collection techniques using documentary analysis and observation sheets. The findings show that the teacher's ability to design learning based on UbD principles through LMS is good. The overall average aspect of the abilities of 30 pre-service teachers is 55% very good, 30.7% good, 11.7% quite good, and only 2.3% were poor, and very poor none. The involvement of pre-service teachers in learning using LMS is good, because more than 85% have actively participated in learning. The implication of this study is to open up new fields of view through modern learning design, provide new learning design when improving the learning process, and provide a potential teacher learning experience when using UbD principles for active learning.